1921 Kan. Sess. Laws 293-94 - (:unkn) unknown (My University, 1921)
§ 4. . . . No person shall use ferrets or employ any smoke gun or other device for forcing smoke or any asphyxiating or deadly gas or liquid into the holes, dens, runways or houses of any fur bearing animals . . . . § 6. . . . [N]o bird be pursued with or shot or killed from a motor boat, or an aeroplane, or with a gun larger than ten gauge
Keywords: HUNTING REGULATION